2003
DOI: 10.1189/jlb.1002507
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib restores expression of CD62L in BCR-ABL-positive cells

Abstract: Chronic myelogenous leukemia (CML) is characterized by aberrant trafficking of malignant hematopoietic progenitor cells in the peripheral blood. Expression of the cell adhesion molecule CD62L was reported to be significantly lower in CML patients than in normal controls. We studied whether the transcription of CD62L in CML cells is dependent on the activity of the BCR-ABL tyrosine kinase. Following addition of the Abelson (ABL) tyrosine kinase inhibitor imatinib (formerly STI571) to two BCR-ABL-positive cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…24 The low levels of expression of adhesion molecules detected in imatinib-resistant patients could be related to their inability to respond to imatinib. Although it seems that adhesion defects in CML may be tyrosine-kinase-independent, 25 restoration of celladhesion molecules may be a mechanism of action of imatinib, as has been demonstrated in in vitro studies by Fruehauf et al 26 for the adhesion molecule L-selectin (CD62L). Likewise, Pelletier et al 27 have suggested that improvement of adhesion between BCR-ABL-expressing myeloid progenitor cells and bone marrow stroma may be of therapeutic value for human CML.…”
Section: Discussionmentioning
confidence: 99%
“…24 The low levels of expression of adhesion molecules detected in imatinib-resistant patients could be related to their inability to respond to imatinib. Although it seems that adhesion defects in CML may be tyrosine-kinase-independent, 25 restoration of celladhesion molecules may be a mechanism of action of imatinib, as has been demonstrated in in vitro studies by Fruehauf et al 26 for the adhesion molecule L-selectin (CD62L). Likewise, Pelletier et al 27 have suggested that improvement of adhesion between BCR-ABL-expressing myeloid progenitor cells and bone marrow stroma may be of therapeutic value for human CML.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Decreased mRNA levels for L-selectin in p210 UCB and early CP CML CD34 þ cells is consistent with published reports demonstrating decreased expression of L-selectin on BM CD34 þ cells derived from CML patients. [38][39][40] We observed populations of CD34 þ cells with higher and lower levels of L-selectin protein expression in primary cells as well as in the UCB transduction model possibly based on subpopulations. Hence, it is possible that the decreased levels of ICAM1 and L-selectin in CML samples is due to skewing of the population away from the population expressing higher numbers of these adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression of E/L-selectin rescued the leukemogenic defect of L-selectin-deficient BM, with 100% of recipient mice developing CML-like leukemia with the same latency as recipients of WT BM ( Figure 6A-B), whereas coexpression of E/Lselectin with BCR-ABL1 in WT BM did not significantly alter the CML-like disease (data not shown). As the chimeric E/L-selectin is resistant to shedding induced by BCR-ABL1, 53 malignant myeloid cells from these leukemic mice expressed human E/L-selectin on their cell surface ( Figure 6D). Importantly, the engraftment defect of the L-selectin-deficient leukemic stem cells was also rescued by coexpression of the stabilized E/L-selectin chimera ( Figure 6E), with an increase in the clonality of the leukemia from 1.2 6 0.4 proviral clones per recipient of L-selectin KO BM to 4.6 6 3.3 clones expressing E/L-selectin (P 5 .028, Student t test).…”
Section: 49mentioning
confidence: 99%